Penerapan Buku Saku “Peduli Stunting” Terhadap Tingkat Pengetahuan dan Sikap Ibu di Wilayah Pinggiran Sungai Kapuas Kota Pontianak - Masmuri, Masmuri; Seprian, Dwin; Limansyah, Dodik; Rusnaini, Rusnaini (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Stunting is one of the problems that exists in communities along the Kapuas River in West Kalimantan. Low levels of knowledge and inadequate attitudes or practices regarding the care of children with stunting are some of the causes of stunting. The characteristics of the people on the banks of the Kapuas River are generally people who are still very closely related to the culture they adhere to. This research aims to examine the effectiveness of implementing the "Peduli Stunting" pocketbook on the level of knowledge and attitudes of mothers with stunted children in the Kapuas River area, Pontianak City. Research method is a quantitative quasi-experiment with a pre-test and post-test with a control group approach with 100 respondents using Total Sampling which is divided into 2 groups (50 respondents in the intervention group and 50 respondents in the control group). The results of the analysis found differences in the level of knowledge and attitudes of mothers before and after intervention with the pocketbook media "Peduli Stunting" with a significant value of 0.000 (p < 0.05). In this study, mothers' knowledge and attitudes cannot be separated from the influence of culture held by marginalized communities Sungai Kapuas which believes that breastfeeding mothers should not give their babies first breast milk because it is thought to contain bacteria and spoiled milk and before they are six months old, babies are given additional food, such as banana "lothe" so that they do not fuss. This research concludes that the pocketbook "Peduli Stunting" increases the knowledge and attitudes of mothers on the Kapuas River in fulfilling and managing the nutrition of children with stunting. In areas where people live on the banks of rivers, there are still many myths and beliefs according to the culture held by the community about what foods can and cannot be given to toddlers. Most of these prohibited foods meet the nutritional needs of toddlers as they grow and develop. The mother's unfavorable attitude is influenced by the culture adopted based on the community's ethnicity. Education with the pocketbook "Peduli Stunting" can be applied Keywords: Stunting, Pocketbook, Knowledge, Attitude  ABSTRAK Stunting merupakan salah satu permasalahan yang ada pada masyarakat pinggiran sungai Kapuas di Kalimantan Barat. Tingkat pengetahuan yang rendah dan sikap atau praktik yang kurang memadai tentang perawatan anak dengan stunting adalah beberapa penyebab terjadinya stunting. Karakteristik masyarakat pinggiran sungai Kapuas juga pada umumnya ialah masyarakat yang masih sangat erat kaitannya dengan budaya yang dianutnya. Tujuan penelitian ini adalah untuk mengkaji efektivitas penerapan buku saku “Peduli Stunting” Terhadap Tingkat Pengetahuan dan Sikap pada Ibu dengan Anak Stunting Di Wilayah Pinggiran Sungai Kapuas Kota Pontianak. Metode Penelitian ini adalah kuantitatif quasy experiment dengan pendekatan pre-test post-test with control group dengan responden berjumlah 100 responden menggunakan Total Sampling yang dibagi menjadi 2 kelompok (50 responden kelompok intervensi dan 50 responden kelompok kontrol). Hasil analisis ditemukan perbedaan tingkat pengetahuan dan sikap ibu sebelum dan sesudah intervensi dengan media buku saku “Peduli Stunting” dengan nilai signifikan yaitu 0,000 (p < 0,05), pada penelitian ini pengetahuan dan sikap ibu tidak lepas dari pengaruh budaya yang dianut masyarakat pinggiran sungai Kapuas yang beranggapan bahwa ibu menyusui tidak boleh memberikan ASI pertama pada bayinya karena dianggap mengandung bakteri dan susu yang basi dan sebelum berusia enam bulan, bayi diberikan makanan tambahan, seperti "lothe" pisang, agar mereka tidak rewel. Kesimpulan dari penelitian ini adalah buku saku “Peduli Stunting” meningkatkan pengetahuan dan sikap ibu pinggiran sungai kapuas dalam pemenuhan dan pengelolaan gizi anak dengan stunting. Pada wilayah lingkungan tempat tinggal yang berada di tepian sungai masih memiliki banyak mitos dan kepercayaan sesuai dengan kebudayaan yang dianut masyarakat tentang makanan apa yang boleh dan tidak boleh diberikan kepada balita. Sebagian besar makanan yang dilarang tersebut memenuhi kebutuhan nutrisi balita saat tumbuh kembangnya. Sikap ibu yang kurang baik dipengaruhi oleh budaya yang dianut berdasarkan suku masyarakat. Edukasi dengan buku saku “Peduli Stunting” dapat diterapkan Kata Kunci: Stunting, Buku Saku, Pengetahuan, Sikap